2009
DOI: 10.1002/prot.22509
|View full text |Cite
|
Sign up to set email alerts
|

Increasing protein stability by improving beta‐turns

Abstract: Our goal was to gain a better understanding of how protein stability can be increased by improving β-turns. We studied 22 β-turns in nine proteins with 66 to 370 residues by replacing other residues with proline and glycine and measuring the stability. These two residues are statistically preferred in some β-turn positions. We studied: Cold shock protein B (CspB), Histidine-containing phosphocarrier protein (HPr), Ubiquitin, Ribonucleases Sa2, Sa3, T1, and HI, Tryptophan synthetase α-subunit (TSα), and Maltose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 66 publications
(77 reference statements)
1
64
0
Order By: Relevance
“…7C), and is likely involved in the stabilization of a β-turn (34). Pro310 contributes a free energy change of −2.38 ± 0.79 kcal/mol towards compaction, all of which is derived from nonpolar interactions due to an increase in the vdW contacts.…”
Section: Resultsmentioning
confidence: 99%
“…7C), and is likely involved in the stabilization of a β-turn (34). Pro310 contributes a free energy change of −2.38 ± 0.79 kcal/mol towards compaction, all of which is derived from nonpolar interactions due to an increase in the vdW contacts.…”
Section: Resultsmentioning
confidence: 99%
“…p à overlap, their angles are not. Bürgi and Dunitz [1] found the best C@OÁÁÁN angle for nucleophilic attack to be 105 ± 5°. AVA displays an angle that is closest to this (96°), followed by GABA (88°), and finally b-alanine (78°).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Pace group [1] showed that protein stability was enhanced by replacing different residues with proline, an amino acid known for promoting n ? p à interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible sites were generally detected in the regions without compacted secondary structures such as β-turns. Sequence statistics collected by Guruprasad and Rajkumar and relative studies indicated that proline is preferred at i + 1 position of Type I and II β-turns and at the i position in Type II β-turns [15,16]. Additionally, since proline is missing amide hydrogen atom, we believe if the wild type residue amide proton is involved in H-bonding, then substitution with proline will lead to destabilization of the protein.…”
Section: Introductionmentioning
confidence: 89%